The Role of Extended Family in Teen Sexual Health. (January 2015) - Grossman, Jennifer M.; Tracy, Allison J.; Richer, Amanda M.; Erkut, Sumru
Despite increasing extended family involvement in child rearing, particularly in minority families, few studies investigate their role in talking with teens about sex or how this relates to teens' sexual behavior. This mixed-methods study assesses extended family sexuality communication through a survey of 1, 492 diverse middle school students and interviews with 32 students. Logistic regression shows that participants who report having had sex are more likely to report talking with extended family than those who report not having had sex. Interview themes explored reasons for and content of teen sexuality conversations with extended family. More sexually active teens' reporting communication with extended family is interpreted as extended family members gaining importance in sexuality communication as teens become sexually active.